Muscle Atrophy Beyond the Clinical Effect After a Single Dose of OnabotulinumtoxinA Injected in the Procerus Muscle: A Study with Magnetic Resonance Imaging - K. Koerte, Inga; Schroeder, A. Sebastian; Fietzek, Urban M.; Borggraefe, Ingo; Kerscher, Martina; Berweck, Steffen; Reiser, Maximilian; Ertl‐Wagner, Birgit; Heinen, Florian (Dermatologic surgery, 2013)
Background Botulinum toxin is a powerful and often used agent to treat dynamic rhytides. Focal and reversible neurogenic atrophy is considered to be the relevant mechanism of action. Objective To investigate the loss and regain of muscular volume in relation to clinical wrinkle severity as assessed using standardized scales. Methods The facial procerus and corrugator supercilii muscles were injected in two drug‐naïve men with 20 U of onabotulinumtoxinA at five injection points (onA). Two men served as controls (one with the same volume of placebo injection using saline solution, one without any intervention). All subjects underwent 3 Tesla magnetic resonance imaging before and after the injection and 1, 4, 6, 10, and 12 months after the injection. Standardized photographs were taken at each test point. Results Volumetric muscle analysis revealed a 46% to 48% reduction in procerus muscle volume lasting for 12 months after a single dose of onA; glabellar line severity returned to the drug‐naïve status after 6 to 10 months. Conclusion The gap between long‐term focal muscular atrophy and regained function remains to be elucidated. Future studies will be needed to investigate the complex interaction between focal neurogenic atrophy and potential compensatory functional muscle changes.